Automatic navigation system for the mouse brain. Issue 13 (24th February 2019) - Tappan, Susan J.; Eastwood, Brian S.; O'Connor, Nathan; Wang, Quanxin; Ng, Lydia; Feng, David; Hooks, Bryan M.; Gerfen, Charles R.; Hof, Patrick R.; Schmitz, Christoph; Glaser, Jack R.
Abstract: Identification and delineation of brain regions in histologic mouse brain sections is especially pivotal for many neurogenomics, transcriptomics, proteomics, and connectomics studies, yet this process is prone to observer error and bias. Here we present a novel brain navigation system, named NeuroInfo, whose general principle is similar to that of a global positioning system (GPS) in a car. NeuroInfo automatically navigates an investigator through the complex microscopic anatomy of histologic sections of mouse brains (thereafter: "experimental mouse brain sections"). This is achieved by automatically registering a digital image of an experimental mouse brain section with a three‐dimensional (3D) digital mouse brain atlas that is essentially based on the third version of the Allen Mouse Brain Common Coordinate Framework (CCF v3), retrieving graphical region delineations and annotations from the 3D digital mouse brain atlas, and superimposing this information onto the digital image of the experimental mouse brain section on a computer screen. By doing so, NeuroInfo helps in solving the long‐standing problem faced by researchers investigating experimental mouse brain sections under a light microscope—that of correctly identifying the distinct brain regions contained within the experimental mouse brain sections. Specifically, NeuroInfo provides an intuitive, readily‐available computer microscopy tool to enhance researchers' ability to correctly identify specific brain regions in experimental mouse brain sections. Extensive validation studies of NeuroInfo demonstrated that this novel technology performs remarkably well in accurately delineating regions that are large and/or located in the dorsal parts of mouse brains, independent on whether the sections were imaged with fluorescence or bright‐field microscopy. This novel navigation system provides a highly efficient way for registering a digital image of an experimental mouse brain section with the 3D digital mouse brain atlas in a minute and accurate delineation of the image in real‐time. Abstract : We developed a novel mouse brain navigation system (NeuroInfo) whose general principle is similar to that of a GPS in a car. NeuroInfo automatically navigates a researcher through the complex microscopic anatomy of histologic sections of mouse brains.